Assortment of black currant cultivars for the Southern Urals - A. A. Vasiliev; F. M. Gasymov; N. V. Glaz (Труды по прикладной ботанике, генетике и селекции, 2020)
The aim of the study was to assess black currant cultivars for yield, environmental plasticity and stability in Chelyabinsk Province. We identified adaptable black currant cvs. ‘Seyanets Druzhnoy’ (4.43 t/ha; AQ = 1.54), ‘Polar’ (3.59 t/ha; 1.38), ‘Venera’ (4.48 t/ha; 1.35), ‘Zhemchuzhina’ (4.49 t/ha; 1.34), ‘Sudarushka’ (4.43 t/ha; 1.30), ‘Bolero’ (3.42 t/ha; 1.20), ‘Gera’ (3.97 t/ha; 1.16), ‘Mortti’ (3.46 t/ha; 1.06), ‘Podarok Ilyinoy’ (3.89 t/ha; 1.03), ‘Selva’ (3.21 t/ha; 1.02) and ‘Mayak’ (3.54 t/ha; 1.01). The most interesting are intensive-type cultivars, capable of significantly increasing their productivity with the improved growing conditions. Intensive-type cultivars developed in Chelyabinsk are cvs. ‘Podarok Ilyinoy’, ‘Sudarushka’, ‘Zhemchuzhina’, ‘Gera’, ‘Mayak’ and ‘Venera’ (bi = 1.70, 1.68, 1.52, 1.46, 1.40, and 1.28, respectively).The locally developed cv. ‘Seyanets Druzhnoy’, environmentally plastic but insufficiently stable (bi = 1.17; Si2 = 6.1), exceeded in its average yield the environmentally plastic and stable cvs. ‘Selva’ (bi = 0.77; Si2 = 0.7) and ‘Mortti’ (bi = 0.93; Si2 = 1.1). Cv. ‘Bolero’ developed by the Vavilov Institute (VIR) and the Swedish cv. ‘Polar’ are neutral, i.e., they weakly respond to changes in cultivation conditions. High yields were recorded for cvs. ‘Zhemchuzhina, ‘Venera’, ‘Sudarushka’, ‘Seyanets Druzhnoy’, ‘Gera’, ‘Podarok Ilyinoy’, ‘Polar’, ‘Mayak’, ‘Mortti’ and ‘Bolero’.The yield of the following cultivars was at the average level for the experiment: ‘Rusalka’ (bi = 1.50), ‘Orloviya’ (bi = 1.56), ‘Pigmey’ (bi = 1.30), plus the yield (3.36 to 3.25 t/ha) of environmentally stable cvs. ‘Legenda’ (bi = 1.24; Si2 = 0.3), ‘Kama’ (bi = 1.00; Si2 = 0.8), and ‘Dochka’ (bi = 1.15; Si2 = 0.5). Cvs. ‘Zem Zarin’ (1.79 t/ha), ‘Chernecha’ (1.82 t/ha), ‘Zorya Galitskaya’‚ (2.18 t/ha), ‘Sibilla’ (2.37 t/ha), ‘Krasa Lvova’ (2.52 t/ha) and ‘Shakhalevskaya’ (2.84 t/ha) demonstrated yield levels significantly lower than the average.